VD_FINDINFO 344 vom 24. Januar 2022 - VD Tribunal cantonal (2022)
COAUTEURDROIT PÉNAL, PRINCIPE DE LA CÉLÉRITÉ, BRIGANDAGE, PRINCIPE DE L'ACCUSATION | 140 ch. 1 al. 1 CP, 325 al. 1 CPP (CH), 5 al. 1 CPP (CH), 9 CPP (CH)